EFEKTIVITAS PELAKSANAAN PROGRAM K3 DI KELURAHAN DUREN JAYA BEKASI TIMUR - Suryani, Elvira (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2015)
Headman leadership involvement to influence the community is needed in order to participate in the implementation of K3 program. Effectiveness of the program can be seen from the high and low levels of leadership and influence public participation in the implementation of the K3 program